Ideological Preferences versus National Integration of India - Vincent, Aparna (Journal of Dharma, 2008)
India is not only diverse in its geographical features, lifestyles of its people and visible symbols, but also in terms of innumerable ideologies and philosophies that have originated in this nation from time immemorial. It can be said that India lives in the minds of its people rather than in its physical boundaries and these varied minds gave birth to a lot of contradictory ideologies and philosophies. When every ideology originated, it had to go through various phases of criticism and, in turn, some other ideologies originated to counter the same. It was the attitude of tolerance that the Indian society showed towards each new trend of thought that made this nation think more and produce more. It is that spirit of tolerance which produced great scholars and philosophers of this country.